Evaluation of the retinal morphological and functional findings in optic neuritis related to multiple sclerosis - Katanić Pasovski, Katarina; Rančić, Nemanja; Pasovski, Viktor; Sajić, Marija; Resan, Mirko; Dinčić, Evica (Vojnosanitetski pregled, 2023)
Background/Aim. Unilateral optic neuritis (ON), and its pathological substrate, retrobulbar neuritis (RBN), is a common presentation of multiple sclerosis (MS). The aim of the study was to determine the diagnostic and prognostic value of structural and functional examination using novel ‘swept-source’ optical coherence tomography (SS-OCT) and OCT angiography (OCTA) techniques in patients with MS who experienced RBN. Methods. For examining retinal structural and functional changes in both the affected and nonaffected eye of patients with MS, novel techniques, OCT and OCTA, were used. The obtained results were compared with the results of the same examination on the left and right eye of the healthy controls. Results. Using OCT, significant differences in the structural integrity and thickness of retinal layers between the eye in which RBN had been detected and the contralateral, nonaffected eye were found (83.73 ± 18.36 vs. 98.67 ± 11.84; p = 0.013). On the other hand, the functional examination of the macular vascular plexus did not show significant differences between the affected and the nonaffected eye in these patients (41.86 ± 1.52 vs. 42.52 ± 1.40; p = 0.228). Interestingly, comparing the nonaffected eye of patients with RBN and healthy controls, a significant difference in the thickness of the retinal layers between the contralateral eye of the patient and both healthy eyes of healthy subjects was found. OCT examination showed particularly significant thinning of the macular ganglion cell-inner plexiform layer (mGCIPL) (61.07 ± 5.04 vs. 67.53 ± 4.57; p < 0.001). Conclusion. Overall, our research showed that OCT and OCTA offer an unprecedented opportunity for a safe, reliable, and repetitive assessment of structural and functional retinal changes as invaluable diagnostic and prognostic tools, paving the way for a better understanding of pathogenic mechanisms underlying inflammatory demyelinating and neurodegenerative diseases. In addition, mGCIPL may be a particularly sensitive and reliable biomarker of pathological changes in MS and perhaps in other neurodegenerative diseases.
Keywords: angiography; diagnosis; multiple sclerosis; optic neuritis; tomography, optical coherence